Minimum Wage and its Functions in Poland - Kisiel, Roman; Orłowska, Magda (Olsztyn Economic Journal, 2015)
The article discusses the issues concerning the minimum wage. Remuneration is the inseparable element of work provided to the employer. Currently, numerous forms and types of it exist, among them the minimum wage which has been the subject of political and media discussions for many years. That subject attracts immense attention and on can find many different and contradictory opinions concerning it. The objective of this article is to draw attention to the issues of minimum wage in Poland analysing the results of own studies that were conducted in 2013. The questionnaire based survey covered 200 respondents, mainly employees, people searching for a job and employers. The questionnaire consisted of 21 questions with the legend (the last 5 questions concerning the sociodemographic situation of the respondents). The minimum wage in Poland is the subject of numerous arguments and disagreements among the employees, trade unions and the government; that is why the article presents not only the principles of minimum wage operation but also the consequences both positive and negative. It also presents the correlation between the costs of work and the minimum remuneration as well as its influence on employment moving from the discussion and analysis of own studies concerning the functioning of the minimum wage in Poland as seen by the unemployed, employees and employers. The vast majority of the respondents (79%) are for the minimum wage increase. And 69% of the respondents believe that the minimum remuneration has the largest influence on the employer.